Leadership Effectiveness in Educational Management in Secondary Schools: A Review of Teacher Perspectives in Indonesia - Suryadi, Yadi; Diding Nurdin; Deisye Supit; Rita Hayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
In education in Indonesia, there is a lack of effective examples provided by leadership in designing learning and implementing it in the field. The aim of this research is to analyze the influence of leadership on changes in secondary schools. The research method used was quantitative involving 562 secondary school teachers as respondents. The sample collection technique was carried out randomly. The data collection technique uses an instrument developed with a rating scale of 1 to 5 points. The data analysis technique is carried out using descriptive statistics with the help of SPSS version 25.0 to calculate the average value and analyze the relationship between variables. As a result, it was found that all dimensions of leadership were at a high category level. The mean showed that teachers' confidence in the implementation of their leadership as a whole was in the good category. These findings indicate that leadership wars make a significant contribution to changes in educational management for the better in secondary schools. The conclusion of this research is that application to leadership needs to be increased in schools and must be sustainable between new and old leaders. So that the effectiveness of learning can be maximized by teachers in junior high schools. The implications of this research indicate the need for training and development from leaders to teachers in junior high schools in improving the quality of planning management and implementation of learning.